Effects of seedling age on the growth stage and yield formation of hydroponically grown long-mat rice seedlings - Yu-xiang LI; Yang LIU; Yu-hui WANG; Yan-feng DING; Shao-hua WANG; Zheng-hui LIU; Gang-hua LI (Journal of Integrative Agriculture, 2020)
Understanding the characteristics of rice productivity is of great importance for achieving high yield formation. However, such traits have not yet been studied for different ages of hydroponically grown long-mat rice seedlings (HLMS), which constitutes a new method of seedling cultivation. Field experiments were conducted to evaluate the effects of seedling age on the growth stage, photosynthesis characteristics, dry matter production, and yield of HLMS. A conventional japonica rice cultivar (Wuyunjing 24) and an indica hybrid rice cultivar (6 Liangyou 9368) were used as test materials. The results showed that the whole phase was shortened by 13–15 days for young seedlings (13-day-old) compared with old seedlings (27-day-old), which occurred because the growth process accelerated with the transplantation of young seedlings. As seedling age increased, the dry matter weight of stems of individual plants and of the population increased at the transplanting stage but decreased at the maturity stage (MS). Compared with that of 27-day-old seedlings, the average ratio of panicle weight to total plant dry weight of 13-day-old seedlings during a 2-year period increased by 3.71% for Wuyunjing 24 and by 3.78% for 6 Liangyou 9368 at the MS. Moreover, as seedling age increased, the leaf area index and photosynthetic potential decreased for both cultivars, and the photosynthetic rate markedly decreased at the heading stage (HS). With the exception of that of Wuyunjing 24 from the jointing stage to the HS in 2014, the crop growth rate was higher for young seedlings than for old seedlings. Grain yield significantly decreased with seedling age, but no significant difference was detected between the 13- and 20-day-old seedlings for either cultivar. Therefore, equilibrious and high biological yield formation, vigorous growth in the late stages, and high photosynthetic production capacity are important characteristics and causes of the efficient and sustainable output of photosynthetic systems and for achieving high yield formation in young transplanted seedlings (13–20-day-old).